2014
DOI: 10.1055/s-0034-1382778
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Third Ventriculostomy for Obstructive Hydrocephalus due to Intraventricular Hemorrhage

Abstract: ETV with or without endoscopic clot evacuation is feasible for patients with hemorrhage-related obstructive hydrocephalus. Potential advantages include avoiding or reducing duration of EVD placement and preventing ventriculoperitoneal shunt placement. Further large prospective randomized trials are needed to evaluate the safety and efficacy of ETV with or without clot evacuation for IVH-related obstructive hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 31 publications
(178 reference statements)
2
26
1
6
Order By: Relevance
“…Obaid et al (23) performed a retrospective analysis of 78 consecutive patients who underwent ETV at their institution. They identified 17 consecutive patients who underwent ETV for obstructive hydrocephalus associated with IVH.…”
Section: Discussionmentioning
confidence: 99%
“…Obaid et al (23) performed a retrospective analysis of 78 consecutive patients who underwent ETV at their institution. They identified 17 consecutive patients who underwent ETV for obstructive hydrocephalus associated with IVH.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the advantage of excellent visualization and illumination, neuroendoscopes allow neurosurgeons to navigate around structures, especially in CSF-filled ventricular system, which made ETV gradually the primary treatment for obstructive hydrocephalus. [1,2] Meanwhile, as experience grows, various studies suggested that complications of ETV increasingly reported and affected the prognosis of patients. [3,4] The complications of the ETV was about 2% to 15%, [5] which included CSF leakage, intracranial infection, intracranial hemorrhage, subdural effusion, postoperative fever, subcutaneous effusion, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] With the wide application of neuroendoscope, complications also gradually increased. [3,4] Cerebrospinal fluid (CSF) leak and subcutaneous CSF collection were one of the most common complications of ETV.…”
Section: Introductionmentioning
confidence: 99%
“…In group B (adult group), however, blood entering the SAS after cerebral hemorrhage is the most likely cause for SAS obstruction. 10 As early as 1932, Dandy cautioned that before performing a third ventriculostomy for obstructive hydrocephalus, it is necessary to establish the patency of distal subarachnoid pathways. The difficulty in preoperatively detecting the presence of coexisting obstruction in the basilar cisterns or in the subarachnoid space of the surface may account for the 25 to 40% failure rate reported in the literature.…”
Section: Discussionmentioning
confidence: 99%